Orangtua yang Lebih Cerdas, Nutrisi Anak yang Lebih Baik? - Syauqan, Teuku Muhammad; Muzayanah, Irfani Fithria Ummul (Jurnal Bina Praja, 2024)
The Indonesian government aims for an ‘Indonesia Emas 2045,’ but child malnutrition remains a major challenge. One important factor that influences malnutrition is parental education level. Previous studies have shown that children’s food consumption is influenced by parental knowledge and education and various interrelated multidimensional factors. This study aims to assess the influence of parental education on improving child nutrition in Indonesia, focusing on developing a model for infants aged 6 to 24 months receiving nutritious complementary foods. The method used in this study was a review of relevant literature. Results show that parental education has a significant influence on increasing the number of infants receiving nutritious complementary foods. In addition, the change in the number of infants consuming nutritious complementary foods is also influenced by several control variables, such as parents’ access to the internet, the impact of smoking among housewives, PKH assistance, parents’ employment status, area of residence, and per capita expenditure. However, this study has limitations as it does not cover the quality and quantity of food consumed by infants, does not consider local cultural influences due to data limitations, and primarily focuses on socioeconomic aspects. Thus, parental education not only improves their access to quality nutritional information but also enriches their knowledge and raises awareness about the importance of nutrition. All these factors cumulatively contribute to improved nutritional intake for children, positively impacting their long-term health.